A MODEL OF THE USE OF INTERNET MEDIA IN READING COMPREHENSION - Sudiran Sudiran (Soegijapranata Catholic University, 2011)
In this rapidly growing world, English plays an important role in the international communication, business and education. Vrielink (2011) said that The Internet is going through a major change with the introduction of social media applications such as Twitter, Blogs, and Facebook. Social media applications are used more and more in our daily personal and professional lives and it seems clear that the way we use the Internet is rapidly changing. This change could have profound implications for the way we use the Internet, for the way we do business, and for the way we learn. The problems of this research are asfollows: I. What is the model of the use of internet media in Englishs subject? 2. How is the students' perception to the importance of internet media in reading course? 3. How important is the internet for the students? 4. How frequent do the students access internet to get meaningful information? In this study, the writer uses descriptive method to find out the answers of the research problems. To get relevant and valid data, the researcher uses structured questionnaires and documentation to reveal the the use of internet model by teachers. Structured questionnaire is used to describe theimportance of internet media in reading subject for the student...,'of SMA Muhammdiyah 1 Kepanjen and SMA Muhammadiyah 2 Sumberpucung. Then, the documentation is used to collect the data that is dealing with the students' frequency to access internet. The result of the study shows that there are three model of internet use at SMA Muhammadiyah I Kepanjen and SMA Muhammadiyah 2 Sumber Pucung East Java. The models are: I) Assignment, 2) Mentoring, and 3) Utilization Function Model. The perception of the students to the importance of internet media is strongly positive. This is suported by 182 students (90.83%) choose option HA